CO 10 - HIPEC: COMO ESCOLHEMOS O PROTOCOLO ANALGÉSICO? - Gonçalo Almeida do Bem1,; Carolina Silva Dias1,; Joana Paulo1,; Joana Oliveira1,; Rui Valente1,; Mercês Lobo1, (Journal of the Portuguese Society of Anesthesiology, 2023)
.